Bovine mycoplasmosis occurrence on livestock farms in the Russian Federation for 2015–2018 - Mohammad Abed Alhussen; A. A. Nesterov; V. V. Kirpichenko; S. P. Yatsentyuk; A. V. Sprygin; O. P. Byadovskaya; A. V. Kononov (Ветеринария сегодня)
Mycoplasmosis control remains urgent in view of wide spread of bovine mycoplasmoses in the countries with intensive animal farming and trade relations between the Russian Federation and foreign partners including import of pedigree livestock and stud bull semen. Results of testing 1,186 biomaterial samples (blood, sera, nasal swabs, milk, preputial swabs, vaginal swabs, aborted and stillborn fetuses) collected from animals that demonstrated clinical signs of respiratory and reproductive disorders in 34 different regions of the Russian Federation for 2015–2018 are presented in the paper. The samples were tested with real-time polymerase chain reaction (rtPCR) for genomes of the following mycoplasmosis agents: Mycoplasma bovis, Mycoplasma bovigenitalium, Mycoplasma dispar. As a result, M. bovis genome was detected in 10.1% of the samples, M. bovigenitalium genome was detected in 8.6% of the samples and М. dispar genome was detected in 37.15% of the samples. Also, 927 semen samples submitted from Russian and foreign breeding farms were tested with PCR. Test results showed presence of M. bovis and M. bovigenitalium genomes in semen samples collected from native bull population. Presented data support Russian scientists’ conclusions on wide mycoplasmoses occurrence in cattle in the Russian Federation territory and risk of the disease agent introduction through semen import. All of these highlight the need for control of semen products as a source for mycoplasmosis spread as well as insufficiency of single testing of semen for granting the disease-free status to the breeding farm for genetic material marketing.